Matemática
kempricardo
2

Sejam as funçoes reais g(x) = 2x - 3 e (f o g) (x)= [latex] 2x^{2}-4x+1 .[/latex] determine a lei da funçao f .

+0
(1) Respostas
andressalopes

[latex]g(x)=2x-3\\ f(g(x))=2x^{ 2 }-4x+1\\ f(x)=ax^2+bx+c\\ \\ f(g(x))=a(2x-3)^2+b(2x-3)+c\\ f(g(x))=a(4x^2-12x+9)+2bx-3b+c\\ 2x^2-4x+1=4ax^2+2(b-6a)x+9a-3b+c[/latex] [latex]4a=2\\ a=\frac { 2 }{ 4 } =\frac { 1 }{ 2 } \\ \\ 2(b-6a)=-4\\ 2b-12a=-4\\ 2b-12(\frac { 1 }{ 2 } )=-4\\ \\ 2b-\frac { 12 }{ 2 } =-4\\ \\ 2b-6=-4\\ 2b=-4+6\\ 2b=2\\ b=\frac { 2 }{ 2 } \\ \\ b=1\\ \\ 9a-3b+c=1\\ 9(\frac { 1 }{ 2 } )-3(1)+c=1\\ \\ \frac { 9 }{ 2 } -3+c=1\\ \\ \frac { 9-6+2c=2 }{ 2 } \\ \\ 3+2c=2\\ 2c=2-3\\ 2c=-1\\ c=\frac { -1 }{ 2 } [/latex] [latex]f(x)=\frac { 1 }{ 2 } x^2+x-\frac { 1 }{ 2 } [/latex]

Adicionar resposta